2005
DOI: 10.1111/j.1423-0410.2005.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HCV and HIV‐1 antibody negative infections in Scottish and Northern Ireland blood donations by nucleic acid amplification testing

Abstract: The SNBTS NAT assays are robust and have performed consistently over the last 5 years. The design of the in-house system allowed HIV NAT to be added in 2003 at a relatively small additional cost per sample, although for both assays, the royalty fee far exceeds the cost of the test itself. Clearly NAT has a benefit in improving the safety of the blood supply although the risks of transfusion-transmitted viral infections, as reported in the Serious Hazards of Transfusion (SHOT) report, are extremely low. Also, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…[23] Jarvis et al ., recommended HIV 4 th generation assays as an alternative to NAT in low prevalence countries as the latter is costly and only reduces but does not completely eliminate the risk of TTHIV infection. [24] In contrast, during a 9 month survey in France covering areas with high HIV seroprevalence, it was observed that 17 patients who were negative for both 3 rd generation ELISA and Western blot tested reactive with 4 th generation ELISA. [25]…”
Section: Discussionmentioning
confidence: 99%
“…[23] Jarvis et al ., recommended HIV 4 th generation assays as an alternative to NAT in low prevalence countries as the latter is costly and only reduces but does not completely eliminate the risk of TTHIV infection. [24] In contrast, during a 9 month survey in France covering areas with high HIV seroprevalence, it was observed that 17 patients who were negative for both 3 rd generation ELISA and Western blot tested reactive with 4 th generation ELISA. [25]…”
Section: Discussionmentioning
confidence: 99%
“…For HIV alone, it is estimated that such testing costs approximately $2 million per quality‐adjusted life‐year and still is unable to completely eliminate viral transmission in the blood supply 27 . Because NAT remains unaffordable in many countries, is time‐consuming, and is labor intensive, and its cost‐benefit in low‐prevalence countries is under review, 28 HIV combination assays could be considered as an alternative to NAT. Such strategies have already been implemented in several countries as the primary method for blood donor screening 15,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to high cost of NAT methods pooled samples (10–96 per pool) [60, 65, 72, 73] are used for donor screening in many of the developed countries [59, 72, 74–76]. Due to the pooling, the samples are diluted, leading to cases where pre-seroconversion donations were negative by both Ab testing and pooled PCR [72, 73, 75, 77, 78].…”
Section: Introductionmentioning
confidence: 99%